Overshoot Nilai Tukar Rupiah Terhadap Us Dollar pada Masa Pandemi Covid-19 - Aji Kristianto, Bima Setyo; Ujang Suherman; Rengga Madya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze overshooting exchange rates Rupiah towards US Dollar during the COVID-19 pandemic period. The data used is monthly data from January 2019 to December 2022. Several variabels employed are exchange rate ,interest rate, inflation, Gross Domestic Product and money supply The analysis methods used include unit root test, lag test, stability test, cointegration test, Granger causality test, Vector Error Correction Model (VECM) estimation, Impulse Response Function (IRF), and Variance Decomposition. The results of the research showed that interest rate and JUB affects significant RP/USD in the long term, whereas in the short term JUB had significant, affects on the exchange value of RP/USD. The VECM estimation results show a significant cointegration relationship, and the response of the variables to the shock reveals the presence of overshooting symptoms. The contribution of these variables to the variability of the Rupiah/USD exchange rate is also identified through the Variance Decomposition test. In conclusion, overshooting in Indonesia during pandemic Covid-19 is occur, by characterizing JUB shock in short term.